Pengaruh Integrasi Tradisi Keislaman Lokal Dan Kurikulum Berbasis Cinta Terhadap Pembentukan Karakter Religius Siswa Kelas Viii Di Mts Darun Najah Bangun Jaya - Fatihatus Sya'adah; Ahmad Zainuri; Mukti Ali (Publikasi Inspirasi Indonesia, 2026)
This study aims to determine the effect of integrating local Islamic traditions and a love-based curriculum on the formation of religious character among eighth-grade students at MTs Darun Najah Bangun Jaya. This research employs a quantitative approach with an ex post facto design. The population consists of 60 students, with a sample of 52 students selected using simple random sampling. Data collection techniques include questionnaires, observation, and documentation. Instrument testing was conducted through validity and reliability tests, while data analysis used multiple linear regression. The results show that the integration of local Islamic traditions has a significant effect on students’ religious character. The love-based curriculum also has a significant effect on students’ religious character. Furthermore, both variables simultaneously have a significant influence on the formation of students’ religious character. This indicates that the integration of local Islamic traditions and a love-based curriculum can create a holistic learning process in shaping students’ religious character. In conclusion, the integration of local Islamic traditions and a love-based curriculum is an effective strategy in improving students’ religious character in Islamic schools.